DISTRIBUSI GOLONGAN DARAH ABO-RH SISWA SDN 3 KETEWEL SUKAWATI GIANYAR - N.M. Linawati; I.G.K.N. Arijana; I.N. Wande; I.W. Sugiritama; I.G.N.S. Wiryawan; I.G.A.D. Ratnayanti; I.A.I. Wahyuniari; D.A.A.S. Laksmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Blood group is one of the identification parameters of a person's identity. Blood group is important to know in relation to medical and non-medical problems. However, there are still many blood group data that are not known to students in Ketewel village. This activity aims to determine the ABO-Rhesus blood group in children at SDN 3 Ketewel. The activity was carried out after coordinating with the Village Head, the headmaster of SDN 3 and also Mantra Medika Clinical Laboratory in Ketewel. Implementation of activities in August 2021 by complying with health protocols during the pandemic of Covid-19. The results of the activity were obtained as many as 65 students consisting of 35 male and 30 female which was 100% positive Rhesus. The distribution of ABO blood typing in male students was 14% A, 25% B, 62% O and 3% AB. Meanwhile, distribution of ABO blood type in female students is 13% A, 33% B and 47% O. From the activity, it can be concluded that the distribution of ABO-Rhesus blood group in SDN 3 Ketewel students is mostly O, the least blood group is AB which were all students Rhesus positive. Keywords: Identification, ABO-Rhesus blood group, SDN 3 Ketewel